Differential Effects of Normoxic versus Hypoxic Derived Breast Cancer Paracrine Factors on Brain Endothelial Cells - Mariam Rado; Brian Flepisi; David Fisher (Biology, 2021)
Background: The blood-brain barrier (BBB) is a central nervous system protective barrier formed primarily of endothelial cells that regulate the entry of substances and cells from entering the brain. However, the BBB integrity is disrupted in disease, including cancer, allowing toxic substances, molecules, and circulating cells to enter the brain. This study aimed to determine the mitochondrial changes in brain endothelial cells co-cultured with cancer cells. Method: Brain endothelial cells (bEnd.3) were co-cultivated with various concentrations of breast cancer (MCF7) conditioned media (CM) generated under normoxic (21% O2) and hypoxic conditions (5% O2). The mitochondrial activities (including; dehydrogenases activity, mitochondrial membrane potential (ΔΨm), and ATP generation) were measured using Polarstar Omega B.M.G-Plate reader. Trans-endothelial electrical resistance (TEER) was evaluated using the EVOM system, followed by quantifying gene expression of the endothelial tight junction (ETJs) using qPCR. Results: bEnd.3 cells had reduced cell viability after 72 h and 96 h exposure to MCF7CM under hypoxic and normoxic conditions. The ΔΨm in bEnd.3 cells were hyperpolarized after exposure to the hypoxic MCF7CM (p < 0.0001). However, the normoxic MCF7CM did not significantly affect the state of ΔΨm in bEnd.3 cells. ATP levels in bEnd.3 co-cultured with hypoxic and normoxic MCF7CM was significantly reduced (p < 0.05). The changes in brain endothelial mitochondrial activity were associated with a decrease in TEER of bEnd.3 monolayer co-cultured with MCF7CM under hypoxia (p = 0.001) and normoxia (p < 0.05). The bEnd.3 cells exposed to MCF7CM significantly increased the gene expression level of ETJs (p < 0.05). Conclusions: MCF7CM modulate mitochondrial activity in brain endothelial cells, affecting the brain endothelial barrier function.